Systemic B-cell lymphoma with preceding myelin oligodendrocyte glycoprotein antibody-associated disease: a case report and literature review - Du, Jing; Cao, Lei; Qi, Xiaokun; Cao, Shugang (Frontiers in Immunology, 2026)
BackgroundThe co-occurrence of myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD) and hematological malignancies is infrequently described. We report a rare case of histopathologically confirmed MOGAD complicated by pancytopenia following corticosteroid therapy, which ultimately unveiled a concurrent systemic B-cell lymphoma.Case presentationA 76-year-old female presented with bilateral lower limb weakness and numbness persisting for two months. She was initially diagnosed with acute myelitis at an external institution and treated with intravenous methylprednisolone (IVMP). A relapse occurred one month after corticosteroid cessation. Upon admission, magnetic resonance imaging (MRI) demonstrated an enlarging spinal cord lesion and extensive enhancement of the cauda equina nerve roots. A spinal cord biopsy revealed necrosis, chronic inflammatory infiltration, and demyelination, without definitive evidence of tumor cells or atypical lymphoid cells. Immunohistochemical staining revealed a loss of MOG expression, while neurofilament (NF) staining confirmed relative axonal integrity with only focal loss within the affected area. The diagnosis of MOGAD was confirmed via cell-based assays, which showed MOG-IgG positivity in both serum (1:32) and cerebrospinal fluid (1:1). However, the patient was refractory to further IVMP treatment and subsequently developed fever and pancytopenia. Peripheral blood immunophenotyping and bone marrow biopsy eventually established a diagnosis of systemic B-cell lymphoma.DiscussionThe coexistence of MOGAD and systemic B-cell lymphoma is rare. This case suggests that MOGAD may serve as a sentinel paraneoplastic manifestation of an underlying lymphoma.